2020
DOI: 10.5114/aoms.2019.88406
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the incidence and prevalence of type 1 and type 2 diabetes among 2 million children and adolescents in Hungary between 2001 and 2016 – a nationwide population-based study

Abstract: The aim of the present study was to assess changes in the incidence and prevalence of type 1 diabetes (T1DM) and type 2 diabetes (T2DM) in children and adolescents in Hungary during the period 2001 to 2016 in order to provide nationwide population-based epidemiology data on diabetes in youths aged 0-18 years. Material and methods: This was a retrospective cohort study of Hungarian children and adolescents aged 18 years or younger. Pharmacologically treated diabetes cases were obtained through a population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 37 publications
2
36
1
4
Order By: Relevance
“…In Hungary, according to the 2019 International Diabetic Federation report, the age-adjusted comparative prevalence of diabetes (type 1 and 2) among the adult population (aged between 20–70 years) is 6.9%, more than 90% of which is accounted for by T2DM [ 32 ]. A recent nationwide population-based study showed that the prevalence of T2DM among children and adolescents in Hungary was 22 out of 100,000 [ 33 ] and this data was higher than in most European countries (such as Denmark [ 34 ] and Germany [ 35 ]). The prevalence of obesity among children or adolescents was 6.6% [ 36 ], while among adults (above 18 years) it was 32% [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Hungary, according to the 2019 International Diabetic Federation report, the age-adjusted comparative prevalence of diabetes (type 1 and 2) among the adult population (aged between 20–70 years) is 6.9%, more than 90% of which is accounted for by T2DM [ 32 ]. A recent nationwide population-based study showed that the prevalence of T2DM among children and adolescents in Hungary was 22 out of 100,000 [ 33 ] and this data was higher than in most European countries (such as Denmark [ 34 ] and Germany [ 35 ]). The prevalence of obesity among children or adolescents was 6.6% [ 36 ], while among adults (above 18 years) it was 32% [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…24 Ezzel összefüggésben új, korábban nem észlelt diabetestípus, a gyermek-és ifjúkori 2-es típusú cukorbetegség észlelése már hazánkban sem számít ritkaságnak. 25,26 Említésre érdemes, hogy 2019-ben tudósítottak először arról az IDF kongresszusán, hogy a világ egyes régióiban (néhány fejlett országban) a 2-es típusú diabetes incidenciacsökkenését lehetett megfigyelni az utóbbi években. A hazai adatbáziselemzés eredményei ezzel összhangban állnak.…”
Section: Ajánlások Rangsorolásaunclassified
“…Adult weight gain has been associated more with visceral adipose tissue in middle age rather than abdominal subcutaneous adipose tissue [4]. Visceral abdominal adipose tissue is associated with complications of hypertension and cardiovascular risk indicators, especially in younger patients and patients with mild-to-moderate hypertension [5,6].…”
Section: Introductionmentioning
confidence: 99%